2013
DOI: 10.1111/vox.12042
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the supernatant of red blood cell units: the effects of storage and leucoreduction

Abstract: Background Red blood cell (RBC) transfusion is a life-saving intervention for critically ill patients; however, it has been linked to increased morbidity and mortality. We hypothesize that a number of important proteins accumulate during routine storage of RBCs, which may explain some of the adverse effects seen in transfused patients. Study Design Five RBC units were drawn and divided (half pre-storage leukoreduced (LR-RBC) and half left as an unmodified control (RBC). The supernatant was separated on days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 50 publications
(71 reference statements)
2
40
0
Order By: Relevance
“…Proteomics on the field blood (plasma) from 2 patients with blunt trauma who later developed ALI/MOF and the plasma from 4 healthy control donors were completed using 2-dimensional gel electrophoresis and mass spectroscopy with computer analyses of the resultant peptides specific for α-enolase (7). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteomics on the field blood (plasma) from 2 patients with blunt trauma who later developed ALI/MOF and the plasma from 4 healthy control donors were completed using 2-dimensional gel electrophoresis and mass spectroscopy with computer analyses of the resultant peptides specific for α-enolase (7). …”
Section: Methodsmentioning
confidence: 99%
“…Repeat ANOVA was performed followed by Neuman-Keuls post-hoc analysis, which was dependent upon the equality of variance. Statistical significance was determined at the p<0.05 level (7). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 We have previously reported that both 5-lipoxygenase and 5-lipoxygenase activating protein are present in RBC units, and their activity likely results in the accumulation of 5-HETE. 36 In addition, there is 12% to 17% sequence homology between human IgG and 5-lipoxygenase activating protein or human IgG and 5-lipoxygenase, which may account for clearance of one of these enzymes by experimental filtration. 37 The PMN priming activity that accumulates in the supernatant during LR-RBC storage is almost totally composed of lipophilic compounds, which were significantly decreased by experimental filtration.…”
Section: Discussionmentioning
confidence: 99%
“…Supernatant of these RBCs also led to significantly higher increase in CD11b expression on freshly isolated neutrophils. Dzieciatkowska et al [6] analysed supernatant of five RBCs in AS-5 that were split with one part pre-storage leucocyte reduced (or leucoreduced). Proteomic analyses of the supernatant were performed on days 1 and 42.…”
Section: Production Process and Storage Solutionmentioning
confidence: 99%